1972
DOI: 10.1139/e72-126
|View full text |Cite
|
Sign up to set email alerts
|

The Continental Margin Off Labrador and Eastern Newfoundland–Morphology and Geology

Abstract: Seismic profiler surveys have defined the landward limit of presumed Mesozoic–Cenozoic deposits on the continental shelf off Labrador and eastern Newfoundland. Along the Labrador coast the contact of these deposits with Precambrian rocks coincides with a pronounced 'marginal channel'; off eastern Newfoundland their contact with rocks of the Appalachian System is marked by a landward-facing escarpment. The physiographic relief characterizing this contact zone reflects erosional exploitation of the associated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Holtedahl (1950Holtedahl ( , 1970) studied marginal channels off glaciated coasts and suggested that they were formed mainly by faulting at the contact between offshore sediments and continental 'shield' rocks. Grant (1971) examined the marginal channel off the Labrador coast and found no evidence of recent faulting. Grant suggested that preferential erosion by glaciation together with a tectonic 'hinge' zone near the contact of Palaeozoic strata with the Precambrian crystalline rocks, were the reasons for the formation of narrow marginal channels off glaciated coasts.…”
Section: A Bathymetry and Physiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Holtedahl (1950Holtedahl ( , 1970) studied marginal channels off glaciated coasts and suggested that they were formed mainly by faulting at the contact between offshore sediments and continental 'shield' rocks. Grant (1971) examined the marginal channel off the Labrador coast and found no evidence of recent faulting. Grant suggested that preferential erosion by glaciation together with a tectonic 'hinge' zone near the contact of Palaeozoic strata with the Precambrian crystalline rocks, were the reasons for the formation of narrow marginal channels off glaciated coasts.…”
Section: A Bathymetry and Physiographymentioning
confidence: 99%
“…The Outer Shelf is underlain by Cenozoic strata (Grant 1971) on which Pleistocene ice sheets deposited a thin veneer of sediments during their retreat (van der Linden et al 1975).…”
Section: Previous Investigations Of Geomorphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The outer shelf consists of shallow banks separated by deep channels cut into the Mesozoic-Cenozoic sequence. A veneer of Pleistocene sediments is recognised by seismic reflection profiling (GRANT, 1972), but its lithology and stratigraphy are virtually unknown. As a result, interpretations of Quaternary glacial ice extent on the North-east Newfoundland shelf are presently poorly constrained (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Labrador inner shelf is studded by a thin cover of till and of sediments derived from till by wave and iceberg reworking (Grant, 1972;Josenhans et al, 1986). The outer shelves of both Labrador and Greenland contain sequences of till and overlying stratified muddy 39 sediments of up to 300 m (Grant, 1972;Funder and Larsen, 1989;Josenhans et al, 1986).…”
mentioning
confidence: 99%